The Potential Inhibition of Xanthine Oxidase by Phenolic and Flavonoids Date (Phoenix dactylifera) with Molecular Docking Method - Akhmad Endang Zainal Hasan; Laksmi Ambarsari; Karichsa Hariana (Indonesian Journal of Applied Research (IJAR), 2021)
Dates is fruit of palm trees that mostly grow in the Middle East. Dates contain phenolic acids and flavonoids that have antioxidants and potentially inhibit the ability of xanthine oxidase. The purpose of this research to determine the molecular interactions of xanthine oxidase by ligand of phenolic acids and flavonoids to inhibiting the production of uric acid. This research was conducted by site directed docking method. The size of the center of retardation used in this research is x = 26.569, y = 9.985, and z = 113.088 and the retardation volume of x = 14, y = 14, and z = 16. Inhibition by flavonoid and phenolic acid compounds has produces good inhibition strength shown by Gibbs free energy which is negative. The compound with the highest Gibbs free energy value is the anthocyanins compound which is -7.3 kCal / mol, the value is higher than the comparator ligand, allopurinol. Based on the bond analysis that is formed, the best compound in inhibiting xanthine oxidase is syringic acid.